Publisher Correction: Morphological, genotypic and metabolomic signatures confirm interfamilial hybridization between the ubiquitous kelps Macrocystis (Arthrothamnaceae) and Lessonia (Lessoniaceae) - Pedro Murúa (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.